Analisis Pelaksanaan Ketidaktepatan Penyimpanan Rekam Medis Pada Bagian Filling di Rumah Sakit - Ririn Afrima Yenni; Linda Handayuni; Dewi Mardiawati; Berly Nisa Srimayarti; Detep Kemalasari (Jurnal Infokes, 2022)
Filling is where outpatient, inpatient and emergency medical records are kept in view of the fact that they are confidential and have a legitimate angle. The motivation behind this investigation is to describe medical records that are not properly placed, lack of storage rack facilities, workload of filling officers and describe the education level of medical record officers. The method used is a literature study by conducting a descriptive analysis by describing the facts that are then analyzed, looking for similarities (Compare), dissimilarities (contrast), views (critize), comparisons (syntheyze) and a summary (summarize) of several studies. This is because the tracer is not used on the storage rack, as well as the lack of facilities and infrastructure such as storage racks and very small storage space. There are officers who have double jobs and the level of education of officers. high school educated. Suggestions from this study are that it is advisable to carry out medical record storage using a tracer, must add medical record officers who are stored so that there is no double job officer and the hospital puts an officer with D3 medical record education in the storage room.